Development and Evaluation of Android-Based Tutorial Learning Media to Improve Student Competence in the Education Dance Course - Mia Fahmiati; Olan Yogha Pratama; Yos Sudarman; Delvia Mona (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2026)
This study aims to develop and evaluate the initial effectiveness of an Android-based tutorial application to support learning in the Dance Education course. The research uses a Research and Development (R&D) approach by adapting the ADDIE model in the Analysis, Design, and Development stages, followed by limited trials as formative evaluation. A total of 30 students from the Dance Education Study Program participated in this study. Data were collected through cognitive competency tests, psychomotor assessment rubrics, observations, interviews, and expert validation. Analysis was conducted using descriptive statistics, paired sample t-tests, Cohen's d, N-gain, and thematic analysis. Validation results indicate good content quality, instructional design, and ease of use (Aiken's V = 0.84–0.93). The use of the application significantly improved students' competencies (t(29) = 12.47; p < 0.001; Cohen's d = 1.94; N-gain = 0.58). The integration of quantitative and qualitative findings provides initial empirical support that the Practice-Based Learning Environment (PBLE) framework has the potential to facilitate the integrated development of cognitive and psychomotor competencies in mobile learning-based dance education.